If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4z + -7)(5 + z) = 0 Reorder the terms: (-7 + 4z)(5 + z) = 0 Multiply (-7 + 4z) * (5 + z) (-7(5 + z) + 4z * (5 + z)) = 0 ((5 * -7 + z * -7) + 4z * (5 + z)) = 0 ((-35 + -7z) + 4z * (5 + z)) = 0 (-35 + -7z + (5 * 4z + z * 4z)) = 0 (-35 + -7z + (20z + 4z2)) = 0 Combine like terms: -7z + 20z = 13z (-35 + 13z + 4z2) = 0 Solving -35 + 13z + 4z2 = 0 Solving for variable 'z'. Factor a trinomial. (-5 + -1z)(7 + -4z) = 0Subproblem 1
Set the factor '(-5 + -1z)' equal to zero and attempt to solve: Simplifying -5 + -1z = 0 Solving -5 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1z = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1z = 0 + 5 -1z = 0 + 5 Combine like terms: 0 + 5 = 5 -1z = 5 Divide each side by '-1'. z = -5 Simplifying z = -5Subproblem 2
Set the factor '(7 + -4z)' equal to zero and attempt to solve: Simplifying 7 + -4z = 0 Solving 7 + -4z = 0 Move all terms containing z to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4z = 0 + -7 -4z = 0 + -7 Combine like terms: 0 + -7 = -7 -4z = -7 Divide each side by '-4'. z = 1.75 Simplifying z = 1.75Solution
z = {-5, 1.75}
| x-32=-5(6x-6) | | 9(-4-p)=3(-4p-8) | | k-8=24 | | 4/17y-16=0 | | ax^2+bs+c=0 | | 7/4=9/r | | 6[5(3-9)-1]+2= | | 7x-2=5x-9 | | f(12)=.25(12-3) | | 8x-1=11x-9 | | 2-u=6 | | -5(1+6X)-8x=38+5x | | 4=2u-2 | | 4i/9-6i | | 0.5p=3.5 | | -x+17+3x+17=-4 | | 3+4y=9 | | 0.25w=16 | | -6k+3=-7-(6k-8) | | 2=2m-2 | | 4x(2x+9)-2(5x+6)= | | 7x+4-3+5-3x= | | 3x-11=-2x-7 | | -16=3-5n+1 | | 18y=6 | | 2*(1200/x) | | 6/m-3 | | 3j-2=14 | | x-6.25=2.5 | | -28x-7y=28 | | 7x+4y-3x+4= | | 13+x(x-13)-(2-5x)=2.8 |